2020
DOI: 10.1177/1049731520905643
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Integrative Body-Mind-Spirit Group Intervention for Parents of Children With Eczema: A Randomized, Wait-List Controlled Clinical Trial

Abstract: Objectives: This randomized controlled trial evaluated the effects of a psychosocial intervention developed based on the Integrative Body-Mind-Spirit (IBMS) model that aimed to enhance the well-being of parents of children with eczema. Methods: Ninety-one families were randomly allocated to either the six-session intervention group ( n = 48) or the wait-list control group ( n = 43) and completed the randomized trial. For both groups, a range of psychosocial outcome measures were taken before the intervention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Many 3 , 22 , 25 , 27 , 29 , 31 , 32 , 34 pointed out that physical, psychological, and spiritual well-being, or body, mind, and spirit, are “interconnected”, “interdependent”, or “interacted”. Although Fung et al 24 mentioned “interconnectedness”, it referred to the interconnectedness of body, mind, and emotional expression, without including spiritual perspective. Xiu et al 35 depicted the “dynamic equilibrium” between body, mind, and spirit in their BMS definition.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many 3 , 22 , 25 , 27 , 29 , 31 , 32 , 34 pointed out that physical, psychological, and spiritual well-being, or body, mind, and spirit, are “interconnected”, “interdependent”, or “interacted”. Although Fung et al 24 mentioned “interconnectedness”, it referred to the interconnectedness of body, mind, and emotional expression, without including spiritual perspective. Xiu et al 35 depicted the “dynamic equilibrium” between body, mind, and spirit in their BMS definition.…”
Section: Resultsmentioning
confidence: 99%
“…Less than half studies 3 , 21 , 23 , 24 , 29 , 32 – 34 exhibited the categorized description of body, mind, and spirit separately. Lau et al 25 only demonstrated body and spirit, but not mind.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations